Theoretical and Practical Aspects of Counteracting Unfair Competition and Violation of Antimononpoly Laws - Korolova, Viktoriia V.; Dolianovska, Inna M.; Hryhorchuk, Myroslav V.; Vyshnevska, Yuliia V. (International Journal of Criminology and Sociology, 2022)
Competition allows business entities to implement projects that can subsequently ensure the development of the socio-public system and the country as a whole. At the same time, an opportunity for personal development is also achieved for a business entity. At the same time, any activity aimed at increasing profitability and market share leads to the emergence of new market participants that can help destabilise the industry or bring innovations to it. This allows the implementation of scientific and technological progress due to the competition mechanism. The novelty of the study lies in the fact that unfair competition is understood only as an element of violation of economically sound norms for entrepreneurial activity. The authors consider the competition of bona fide type as an element of the formation of saturation of the commodity market. Moreover, the state is considered not only as a source of antimonopoly legislation, but also as a factor in the implementation of the principles of competition in the interests of society as a whole. The practical significance of the study is determined by the possibility of structuring the requirements for competition law on the basis of independent regulation and the additional use of judicial and restrictive measures to spread the practice of competition in any sector of the national economy.